Performance measurement system effectiveness in public sector IT outsourcing contracts - Perrin, Brian; Pervan, Graham (Cranfield University, 2009)
A key issue in the successful management of an Information Technology (IT) outsourcing contract is the measurement of the vendor's performance to ensure that all agreed outcomes are achieved. An effective performance measurement system (PMS) provides both control and accountability of the vendor and the contract arrangements. Despite the recognised importance of performance measurement to the overall success of IT outsourcing, a review of the literature highlights that research in this area is very limited. Based on a survey of large public sector organisations and universities throughout Australia, this paper develops and explores a three-dimensional model initially developed by Bouckaert (1993) and later refined by Streib and Poister (1999) to measure the effectiveness of performance measurement systems used in public sector IT outsourcing contracts. This research supports Bouckaert's (1993) proposition that an effective performance measurement system needs to include three essential characteristics : be valid, legitimate and functional. This research contributes to the existing literature on the choice and implementation of PMSs used in public sector IT outsourcing service contracts, and provides some practical guidance to public sector managers on the design of effective PMSs. The results also highlight that an effective PMS is a dynamic process that is not static and should be continually improved